Effects of soy milk ingestion on running anaerobic sprint test (RAST) performance - Pan, Shi Yu (2018)
Co-ingestion of carbohydrate and protein (CHO-PRO) pre-exercise has been found to exert ergogenic effects in terms of glycogen sparring, protein resynthesis and rehydration. Recent studies on milk and soy proteins reported improved performance and recovery post-exercise, but most involved endurance or resistance exercise. The limited studies on soy proteins with intermittent anaerobic exercises warrants for further investigation. This study aims to investigate the effects of soy milk on anaerobic performance using the repeated anaerobic sprint test (RAST). In a randomized, experimental design, 10 healthy males (23.2 ± 1.23 years) were recruited to perform two RAST with a soy milk intervention (SOY: 500mL soy milk + 4g stevia sweetener) and a placebo control (CON: 500 mL water + 4g stevia sweetener). The RAST consists of six 35 m sprints with 10 seconds recovery between each sprint. Final timings of each sprint were recorded. Heart rate, rating of perceived exertion, rating of hunger and fullness, blood glucose and lactate levels were recorded. Peak power output and fatigue index were studied in relation to the velocity and body mass of the individual. Fatigue index in SOY trial (p = 0.023) was significantly lower than in CON trial. Mean power output (p = 0.410) and relative power output (p = 0.461) between trials were not significant. Blood lactate (r = - 0.654) and glucose (r = - 0.662) levels were inversely associated with mean power output in the SOY trial. Soy milk ingestion pre-testing significantly reduced fatigue but did not significantly increase power production.